PEMBERDAYAAN MASYARAKAT MELALUI PENGEMBANGAN AGROWISATA BERKONSEP GREEN MARKETING (ORGANIK) DI KECAMATAN LICIN - galih satriyo; Suwarso Suwarso; Fandi Ahmad; Saiful Rohman (Jurnal Bisnis Terapan, 2020)
The geographical condition of the Banyuwangi district 5,782.50 km2 is partly a forest area. One element of the agricultural sector that has not been explored optimally is agro-tourism. The physical potential of the Banjar and Segobang Villages has volcanic and Alluvial types which are very fertile because they are located on the slopes of Mount Ijen. The purpose of this research is to encourage the people of Segobang Village and Banjar Village, Licin District to optimize their agricultural land so that they have added value by realizing agro-tourism through community empowerment. The method in this study uses qualitative methods. The results of this study are that farmers need guidance to manage agricultural businesses into tourism businesses, so it is not only limited to how to meet food needs. Village parties need to promote through social / web media, print media and festivals. The potential of each village needs to be combined with branding, Segobang Village with "MINA UMBAR" branding and Banjar Village with "JEMALI" Licin Sweet Orange Branding. Building a network between farmers and several resorts and homestays around the villages of Banjar and Segobang also needs to be done with the aim of good fish, organic rice, palm sugar and slippery oranges can be used as souvenirs and food and beverage menu items.